FLT3-ITD promotes immune checkpoint CD80 via ROS elevation in acute myeloid leukemia - Yan, Libo; Zhang, Weiming; Mo, Qiyan; Wang, Daogang; Xu, Ning; Yang, Mengzhe; Ren, Tao (Frontiers in Immunology, 2025)
Acute myeloid leukemia (AML), a malignant hematological stem cell disease, arises from the malignant transformation of myeloid progenitor cells. Among the genetic aberrations in AML, mutations in the tyrosine kinase receptor FLT3, especially FLT3-ITD, are most frequently detected and are correlated with poor clinical outcomes. Intriguingly, FLT3-ITD is implicated in immune escape, although the underlying mechanism remains elusive. The present study aims to elucidate the relationship between FLT3-ITD and the immune checkpoint molecule CD80, which is crucial for immune regulation. Our results provide compelling evidence that a moderate level of CD80 localizes on the cell surface of FLT3-ITD AML cells. Mechanistically, FLT3-ITD upregulates CD80 expression by increasing intracellular reactive oxygen species (ROS) levels and subsequent CD80 enhancement. Significantly, we found that treatment with a HIF-1α inhibitor selectively suppressed the proliferation of FLT3-ITD-positive leukemic cells and induced excessive ROS production, which consequently led to CD80 overexpression. Collectively, our findings unravel the molecular pathway through which FLT3-ITD augments CD80 expression via ROS, suggesting a potential immune evasion. Moreover, this study points to a novel therapeutic strategy that combines chemotherapy-induced CD80 overexpression with immune checkpoint-targeted immunotherapy to eradicate FLT3-ITD AML cells.